Conceptual Analysis of the High-Touch, High-Tech Trend: The Suitability of Technology for Tourism Transformation in Rural Destinations - Supina, Supina; Dewantara, Yudhiet Fajar; Krisnadi, Antonius Rizki (Institut Pariwisata Trisakti, 2024)
This research aims to evaluate the role of technology in rural tourism development, focusing on the match between technology and the capabilities of local communities. The method used is a quantitative approach, namely data collection through questionnaires distributed to three groups of respondents: local communities, technology providers and tourists. Two main research questions were identified: (1) Is the technology applied by the community service capacity in the tourist village? (2) How can technology be adapted to the needs of local communities and the experiences tourists desire? The research results show that appropriate technology can improve tourist experiences and empower local communities. However, reliance on technological trends without a strong foundation can decrease tourist interest. Therefore, this research concludes that the application of technology must be based on a deep understanding of the local context to avoid inappropriate investments and maintain tourism sustainability. These findings provide important insights for stakeholders in designing appropriate technology strategies for tourist villages. Keywords: rural tourism, technological progress, high technology, emerging markets, tourism services